Francofonía y literatura: análisis del cuento “Khary-Gaye” de Birago Diop - Méndez Vega, Mauricio M. (2013)
This article begins with a general introduction to the concept of “Francophonie” (its origins and the different geographic regions that it comprises, in the framework of the Research Project about the main XXth and XXIst century writers belonging to “Francophonie”); after that, there is a brief presentation of the Senegalese author Birago Diop and it ends with a succinct analysis of his tale “Khary-Gaye”.